2004
DOI: 10.1037/0022-0663.96.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Reading Comprehension and Engagement Through Concept-Oriented Reading Instruction.

Abstract: Based on an engagement perspective of reading development, we investigated the extent to which an instructional framework of combining motivation support and strategy instruction (Concept-Oriented Reading Instruction-CORI) influenced reading outcomes for third-grade children. In CORI, five motivational practices were integrated with six cognitive strategies for reading comprehension. In the first study, we compared this framework to an instructional framework emphasizing Strategy Instruction (SI), but not incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
369
1
37

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 564 publications
(483 citation statements)
references
References 59 publications
25
369
1
37
Order By: Relevance
“…Together with other products from the thematic unit, the revised texts are prepared for presentation, often to an audience of parents and students from other groups (Van Rijk et al, forthcoming). From this overview, it may be clear that DE incorporates motivational practices that are similar to those of CORI (Guthrie et al 2004). In Figure 1, we describe the differences between PI and DE.…”
Section: Programmatic Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with other products from the thematic unit, the revised texts are prepared for presentation, often to an audience of parents and students from other groups (Van Rijk et al, forthcoming). From this overview, it may be clear that DE incorporates motivational practices that are similar to those of CORI (Guthrie et al 2004). In Figure 1, we describe the differences between PI and DE.…”
Section: Programmatic Instructionmentioning
confidence: 99%
“…The effortful and deliberate processes of strategic behaviour in their turn lead to understanding a text and, ultimately, to reading competence (see for a fine-grained discussion and evidence Guthrie, Wigfield, and You 2012). Motivation is enhanced by a number of motivational practices, such as (1) the integration of reading and strategy instruction in domain-specific content matters, (2) the provision of interesting texts to strengthen relevance and the value of reading, (3) text choices to support autonomy and intrinsic motivation, (4) positive feedback regarding comprehension for self-efficacy, (5) the organisation of collaboration to enhance social motivation in sharing cognitive activity (Guthrie and Klauda 2014;Guthrie et al 2004).…”
Section: Content-oriented and Strategy Approaches To Reading Comprehementioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical studies now suggest that integrated approaches can improve student outcomes on science and literacy measures (e.g., Cervetti et al, 2012;Fang & Wei, 2010;Greenleaf et al, 2011;Guthrie et al, 2004;Purcell-Gates, Duke, & Martineau, 2007;Vitale & Romance, 2012). In a systematic review on quasi-experimental studies of integrated scienceliteracy instruction, Bradbury (2014, p. 483) noted that the reviewed studies "indicated positive outcomes for student achievement in both science and reading, as well as for affective factors".…”
Section: Integrated Science-literacy Instructionmentioning
confidence: 99%
“…Toutefois, un certain nombre d'études ont montré qu'un entraînement des stratégies d'apprentissage et une prise de conscience de son propre fonctionnement cognitif permettaient d'améliorer la compréhension de texte chez des élèves en difficulté (Büchel et Molo, 2000;De Corte, Verschaffel et Van De Ven, 2001;Guthrie, Wigfield et Perencevich, 2004;Tonks et Taboada, 2011 Hattie, Biggs et Purdie, 1996) Büchel, 2008Büchel, Berger, Kipfer et Frauchiger, 2010;Büchel, Grassi, Scharnhorst et Ghilardi, 2002 (Büchel, 2013). [Büchel et Büchel, 1995] 2 Le PEI est un programme d'éducation cognitive qui vise à favoriser le développement du fonctionnement cognitif nécessaire à l'apprentissage et à la réussite scolaire.…”
Section: Introductionunclassified